Les archives administratives de l'Ancien Empire - Collombert, Philippe, 1969-; Tallet, Pierre, 1966- (Orient & méditerranée ;, 2021)
This collective volume presents the proceedings of an international symposium co-organized by Sorbonne university and Geneva university in Paris between February 12th and 15th 2015. The aim of the such a meeting was to establish a "state of the art" of the papyrological documentation known to us for this specific period of pharaonic history (letters, accounting documents, inventories, working teams' logbooks, personnel registers). By bringing together most specialists of this type of historic sources, it has enabled a complete presentation of the main series of documents from the Memphite area (papyri of Abusir and Sakkara), from Upper or Middle Egypt (Meir, Sharuna, Gebelein, Elephantine), or even from more remote places like the wadi el-Jarf harbour on the Red sea shores or Balat-Ayn Asil archives in the Dakhla oasis. Each contributor gives an overview of the available documentation and the most recent studies related to it. Numerous examples, some of them hitherto unpublished, are illustrated in this volume so as to better understand the way those lots are organized and to fully apprehend how the administration of this period was managed at the provincial as well as central level.